Lockdown and Rural Joblessness in India: Gender Inequality in Employment? - Nabamita Dutta; Saibal Kar (Institute of Labor Economics (IZA), 2022)
India experienced one of the strictest lockdowns during COVID-19 and sections of the workforce seemed overwhelmingly disadvantaged. Given substantial poverty still, marginalized daily wage labor and gendered outcomes in the context of India, economic shocks are expected to have disparate implications. Employing World Bank data for rural areas in six states of India, we investigate the probability of female employment during the lockdown period between March and May 2020. Based on marginal estimates of logit specifications, our results show that females, in general, were 8 percent less likely to be employed as compared to males. Females belonging to marginalized castes experienced higher likelihood of being unemployed – between 9 and 14%. Return migrants generally suffered less in terms of finding alternative jobs at the source, but being a female return migrant, the probability of joblessness rises to about 17%. For female return migrants belonging to marginalized castes, the probability of joblessness is about 10%. Lockdown is expected to have raised the economic inequality by gender and needs commensurate interventions.
Keywords: J16; F22; E24; C33; 330; COVID-19; lockdown; gender; unemployment; return migrants; India